Synthesis of Defective MOF-801 via Air–Liquid Segmented Flow for Catalytic Transfer Hydrogenation of Furfural - Yuxuan Liu; Qiuju Fu; Weijing Niu; Yingxin Zhang; Wenpeng Xie; Huimin Jiang; Liting Yan; Guangda Li; Xuebo Zhao (Molecules)
As one of the most important platform chemicals, furfural (FAL) can be converted into high-value-added products such as furfuryl alcohol (FOL) through multiple pathways. Zirconium-based MOF-801 demonstrates exceptional catalytic potential for FAL conversion via catalytic transfer hydrogenation (CTH), owing to its unique crystal defects generated during growth. In this study, a series of defective MOF-801 samples were efficiently synthesized using an air–liquid segmented microfluidic technique. The characterization results reveal that the air–liquid segmented flow method not only regulates the defect content of MOF-801 to expose more active sites but also adjusts the crystal size and pore structures by precisely controlling the reaction time. The enhanced defects in MOF-801 significantly improved its catalytic performance. A-MOF-801-64 exhibited the highest activity, achieving over 99% FAL conversion and 98% FOL selectivity under mild conditions (130 °C, 12 h) using isopropanol as the hydrogen donor; this performance surpassed that of other reported Zr-based catalysts. This study will facilitate the practical applications of defect-engineered MOF-801 in upgrading biomass-derived chemicals.